Evaluation of the recognition of Theileria parva vaccine candidate antigens by cytotoxic T lymphocytes from Zebu cattle - Akoolo, L.; Pelle, Roger; Saya, R.; Awino, Elias; Nyanjui, J.; Taracha, E.L.N.; Kanyari, P.; Mwangi, David Miano; Graham, S.P. (Elsevier, 2008)
East Coast fever (ECF) is a highly fatal lymphoproliferative disease of cattle caused by Theileria parva, a tick-borne intracellular apicomplexan parasite. Parasite antigens that are targets of protective cytotoxic T lymphocyte (CTL) responses are required to formulate a sub-unit vaccine against ECF. A number of CTL target antigens have recently been identified and initial evaluation has shown their vaccine potential. This study aimed to evaluate whether these antigens were recognised by CTL obtained from six genetically diverse Zebu cattle immunized with a cocktail of T. parva stocks. T. parva Muguga specific polyclonal CD8(+) CTL lines were generated and confirmed to specifically lyse autologous infected cells. CTL recognition of autologous skin fibroblasts (iSF) transduced with recombinant modified vaccinia virus Ankara strain (MVA) expressing previously identified T. parva Muguga vaccine candidate antigens was evaluated using an IFN-gamma ELISpot assay. CTL lines from one of the four calves, BY120, responded specifically to cells infected with MVA expressing the antigen Tp2 and synthetic peptides were employed to map a new CTL epitope on this antigen. Immunoscreening of the T. parva genome with these CTL lines should identify novel antigens that will constitute valuable additions to the vaccine candidates currently being evaluated.